2013
DOI: 10.1111/pedi.12009
|View full text |Cite
|
Sign up to set email alerts
|

The relation of serum nesfatin-1 level with metabolic and clinical parameters in obese and healthy children

Abstract: This is the first study to evaluate nesfatin-1 levels in relation with anthropometric and metabolic parameters in obese patients who had significantly lower nesfatin-1 levels. Our results underline that nesfatin-1 may play an important role in regulation of food intake in obese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
2
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 39 publications
3
39
2
9
Order By: Relevance
“…A strong correlation has been reported between N1 and pro-inflammatory cytokines [32,33]. There are studies reporting the association between the low N1 levels and the elevated systolic and diastolic BP [34]. Although basal N1 levels have an anti-inflammatory effect, its low-level increases inflammation, possibly leading to the development of hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…A strong correlation has been reported between N1 and pro-inflammatory cytokines [32,33]. There are studies reporting the association between the low N1 levels and the elevated systolic and diastolic BP [34]. Although basal N1 levels have an anti-inflammatory effect, its low-level increases inflammation, possibly leading to the development of hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, in obese subjects nesfatin-1 was negatively correlated with the BMI. 15 Moreover, Tsuchiya et al reported that fasting nesfatin-1 level was significantly lower in subjects with high BMI than in non-obese subjects, and the peripheral concentration of nesfatin-1 showed a negative correlation with BMI, percentage of body fat, body fat weight and blood glucose. 5 In patients with nonalcoholic fatty liver disease, serum nesfatin-1 level in the obese group was significantly lower than in the non-obese group.…”
Section: Discussionmentioning
confidence: 99%
“…Kaba et al (12) found no significant association between BMI SDS and nesfatin-1 (neither in underweight children nor in control groups), while Kahraman et al (13) demonstrated a positive correlation between BMI SDS and nesfatin-1. Similarly, conflicting results regarding the nesfatin-1 level were observed in studies performed in obese children (32)(33)(34). Abaci et al (32) previously reported lower serum nesfatin-1 levels in obese subjects compared to those of healthy controls and a negative correlation between nesfatin-1 and BMI in nonobese males.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, conflicting results regarding the nesfatin-1 level were observed in studies performed in obese children (32)(33)(34). Abaci et al (32) previously reported lower serum nesfatin-1 levels in obese subjects compared to those of healthy controls and a negative correlation between nesfatin-1 and BMI in nonobese males. In addition, it has been speculated that low levels of this satiety peptide may be one of the reasons for inadequately controlled food intake.…”
Section: Discussionmentioning
confidence: 98%